Kepemimpinan Profetik dalam Menumbuhkan Kakarakter Peserta Didik - Moh. Syamsul Falah; laily masruroh; Iva inayatul Ilahiyah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
The prophetic leadership model is a leadership modelthat is rarely studied. This leadership model is very suitable to beapplied in various situations. Generally, the leadership modelprioritizes scientific and experiential aspects only. Meanwhile,this prophetic leadership model requires a leader not only tohave scientific and practical abilities but also to have a strongfaith or spirituality. This prophetic leadership is more attached tothe uswah of the leader as the principal of the school, its abilitywhich is driven from the aspects of high conscience and logic (intellectual intelligence) makes it easy for leaders to achievesuccess because what is dynamized is truth and intelligence.Such a leader's attitude makes motivation and inspiration forsubordinates in shaping their character, including students inschool. Based on the identification of the problems above, theresearcher wants to answer the focus of the research question,namely, how is prophetic leadership in fostering the character ofstudents in school? The method of this research was carried outby library research (library research) as part of the qualitativeresearch design. While data collection is carried out byresearchers by collecting information that is relevant to theresearch context. This information can be obtained byresearchers through books, scientific papers, and journals.